An evaluation of the performance of the housing finance system in the Kingdom of Saudi Arabia. Issue 2 (27th May 2014) - Sidawi, Bhzad
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aim of this paper is to find ongoing socioeconomic needs and how they affect the built environment and how they should be financed. Design/methodology/approach – A field survey was undertaken in 2011 in the eastern province of the Kingdom of Saudi Arabia (KSA) to find the citizens' views about the initial and ongoing financial support of banks and the real estate development fund. Findings – The survey's results showed that the majority of the respondents did not manage to take up mortgage and own a property. There is also serious lack of financial support for the population's socioeconomic needs. Research limitations/implications – The research is carried out in the KSA. The findings, however, can be generalized to other Gulf and Islamic countries as well. Practical implications – The research would enable the policymakers and financing bodies to consider future socioeconomic needs of low-income citizens and set proper financial resources to meet these needs. Originality/value – Few research studies have been carried out in the KSA in regard to the relation between the built environment and ongoing socioeconomic needs.